2018
DOI: 10.1007/s10620-018-4989-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Outcomes of Hospice Utilization Among Patients with Advance-Staged Hepatocellular Carcinoma in a Veteran Affairs Population

Abstract: Background Hospice provides integrative palliative care for advance-staged hepatocellular carcinoma (HCC) patients, but hospice utilization in HCC patients in the United States is not clearly understood. Aims We examined hospice use and subsequent clinical course in advance-staged HCC patients. Methods We conducted a retrospective study on a national, Veterans Affairs cohort with stage C or D HCC. We evaluated demographics, clinical factors, treatment, and clinical course in relation to hospice use. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Our analysis also compared ESLD with other major causes of death and found that although ESLD had the second highest proportion of deaths in hospice, it still substantially trailed malignancy. Based on previous studies in cancer populations, ( 29,44,45 ) we expected and found that patients who died with HCC and non‐HCC malignancy had significantly higher rates of death at hospice and home than other diseases. Death attributed to infection, on the other hand, occurred more often in an inpatient setting, which may be because infections are felt by many to require hospitalization.…”
Section: Discussionmentioning
confidence: 98%
“…Our analysis also compared ESLD with other major causes of death and found that although ESLD had the second highest proportion of deaths in hospice, it still substantially trailed malignancy. Based on previous studies in cancer populations, ( 29,44,45 ) we expected and found that patients who died with HCC and non‐HCC malignancy had significantly higher rates of death at hospice and home than other diseases. Death attributed to infection, on the other hand, occurred more often in an inpatient setting, which may be because infections are felt by many to require hospitalization.…”
Section: Discussionmentioning
confidence: 98%
“…Another study by Zou et al . of the United States Veteran Affairs database identified 814 patients with advanced ( n = 564) or terminal ( n = 250) stage HCC 61 . The authors found 40.8% of patients entered hospice care (and hence received palliative care involvement) directly after HCC diagnosis.…”
Section: Role Of Palliative Care In Hepatocellular Carcinomamentioning
confidence: 99%
“…The implementation of palliative care for HCC is hindered by factors including lack of resources, stigmatization, and physician‐associated barriers 61,62,66,70,79 (Table 3). Several studies in the United States have also identified cultural, language, and insurance barriers to accessing palliative care in ESLD, with lower referral rates seen in non‐Caucasian and uninsured populations 68,69 …”
Section: Current Barriers To Early Palliative Care Interventionmentioning
confidence: 99%
See 2 more Smart Citations